EFFECTIVE WAYS OF TEACHING AND EXPANDING VOCABULARY (ResearchJet Journal of Analysis and Inventions, 2021)
This article studies the importance of vocabulary, the effective methods of teaching and the ways of developing them. In addition, it gives several essential information about some methods of expanding vocabulary.